Al-Qur'an Views Relating to Environmental Conservation - Ariyadi Ariyadi (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
Allah SWT has created a variety of nature on this earth. The plant that God created with various benefits. Wrong is for human needs. Humans as God's creatures also need plants for them. In fact, the essence is the most perfect worshiper of God, but they will still need the plant. The universe is the greatest gift to man, for that Allah Almighty enjoined man to make good use of it and we must continue to give thanks to Him. In reality, however, there is corruption here and there from the actions of the hypocrites. Human beings as perfect beings who are mind-wielded by God should use their reason for everything good for themselves and for others. Including plant or tree maintenance for the sake of their environmental sustainability. In addition, we also should not neglect the land because the land can be used for something good. the environment taught by Rasulullah SAW based on revelation, so many we encounter scientific verses of the Qur'an that discusses the environment. The Quranic messages about the environment are very clear and perspective. This authors' journal will try to discuss extensively al-Quran and the environment, since al-Qur'an has explained the importance of safeguarding the environment by laying its foundations and principles globally. Purpose of problem First: Knowing what and how the current environmental condition. Second: Knowing how important it is to maintain and maintain the environment. Third: Know how to keep the environment as it is in al-Qur'an.